Proof for a Case where Discounting Advances the Doomsday - Koopmans, Tjalling C. (Review of Economic Studies, 1974)
Proof for a Case where Discounting Advances the Doomsday Get access Tjalling C. Koopmans Tjalling C. Koopmans International Institute for Applied Systems Analysis Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 41, Issue 5, December 1974, Pages 117–120, https://doi.org/10.2307/2296375 Published: 01 December 1974